In vitro susceptibility profiles of 16 antifungal drugs against Trichophyton indotineae - Wenting Xie; Xue Kong; Hailin Zheng; Huan Mei; Naicen Ge; Weida Liu; Guanzhao Liang; Xiaofang Li (Microbiology Spectrum)
ABSTRACT The worldwide emergence of Trichophyton indotineae has garnered significant attention due to its growing resistance to conventional antifungal therapies, posing significant challenges to the effective management of dermatophytosis. The in vitro activities of 16 antifungals were tested against 37 T. indotineae isolates using the broth microdilution method according to Clinical and Laboratory Standards Institute protocol M38-A3. Luliconazole and amorolfine exhibited low MICs, while itraconazole showed moderately decreased susceptibility, making them preferred treatment options. Echinocandins demonstrated favourable in vitro activity against T. indotineae, but their potential as therapeutic alternatives for recalcitrant dermatophytosis remains uncertain due to pharmacokinetic and pharmacodynamic limitations. In contrast, terbinafine, fluconazole, griseofulvin, oteseconazole, isavuconazole, ravuconazole, and amphotericin B exhibited elevated MICs for many strains, with strong correlations between certain azoles, indicating potential cross-resistance. A difference in the susceptibility to terbinafine and voriconazole between Chinese and Indian isolates was observed. These findings could provide valuable insights into antifungal resistance patterns and help guide treatment strategies for T. indotineae infections.IMPORTANCETrichophyton indotineae is a novel emerging dermatophyte that has rapidly spread globally in recent years. Its resistance to first-line antifungal agents, particularly terbinafine and fluconazole, has significantly limited treatment options, emphasizing the urgent need for alternative therapies. This study provides comprehensive antifungal susceptibility data for 16 available antifungal agents, offering valuable insights into potential treatment strategies.